The Influence of Whiteness on Female Gender Roles: a Study of Race, Class, and Gender in Sula, The Awakening, and The Handmaid's Tale - McIntosh, Jennifer (My University, 2012)
In this thesis I explore how Toni Morrison, Kate Chopin, and Margaret Atwood use the central female characters in their respective novels, Sula, The Awakening, and The Handmaid's Tale, to showcase the intricate relationship between race, class, and gender as it relates to the struggle to break free from society's expectations. Differences in race and levels of class allow for small glimpses of freedom, but in reality the possibility of true freedom is simply an illusion. From the perspective of Sula, Edna, and Offred, the ability to transcend the expectations society has placed upon them, which varies based on class and race, and create a unique self would mean achieving true independence. In their novels, Morrison, Chopin, and Atwood stress the dangers that lie within this puzzle of male domination, class rank, and white privilege. I contend that this danger is the incongruence that exists between society's view of female independence and its meaning to these women. I also argue that the dominant race and class, white, middle-class society, controls the illusions of freedom. As long as the female characters play within the boundaries approved by the "white norm," those around them will view their actions as the harmless testing of boundaries and as meaningless play, but, to these female characters, their actions reflect willful and serious struggles to gain autonomy and freedom. As these women push the boundaries, they go through a journey of realization. Through the analysis of the novels, it is clear that these women are not naive in terms of their limitations as women, but because their respective societies allow them to "play" within the confines of their gender, early in the novels they believe they can actually transcend their socially assigned gender roles, but they do not understand the relationship between their class, gender, and race and the power which white privilege has in controlling their freedom. As all three women progress toward what they believe to be a true, independent self, they begin to see the relationship between their class, race and gender and the unique challenges they face because of these social markers. Ultimately, these women come to realize that although race, class, and gender provide unique experiences for them, it is the power of white, middle-class society that holds them back. Ultimately, once these women realize their experiences will never result in true independence as long as white, middle-class society determines their boundaries, they find little hope for the future.
A Thesis Submitted In Partial Fulfillment of the Requirements For the Degree of Master of Arts-English
Keywords: Race in literature; Married women; Wives; Women in literature; Social classes in literature